Case Reporting in Homeopathy—An Overview of Guidelines and Scientific Tools - Teut, Michael; van Haselen, Robbert A.; Rutten, Lex; Lamba, Chetna Deep; Bleul, Gerhard; Ulbrich-Zürni, Susanne (Homeopathy, 2021)
Case reports have been of central importance to the development of homeopathy over the past 200 years. With a special focus on homeopathy, we give an overview on guidelines and tools that may help to improve the quality of case reports. Reporting guidelines such as CARE (Case Report), HOM-CASE (Homeopathic Clinical Case Reports), and the WissHom Documentation Standard help to improve the quality of reporting and strengthen the scientific value of a case report. Additional scientific tools such as prospective outcome assessment, prognostic factor research, cognition-based medicine, and the Modified Naranjo Criteria for Homeopathy (MONARCH) score may be helpful in improving case documentation and evaluation.
Keywords: homeopathy; case reporting; guidelines; case research